Analisis Kinerja Keuangan pada PT Lontar Papyrus Pulp dan Paper Industry - Miftahur Rezqi; Efni Anita; Mohammad Orinaldi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
His thesis aims to find out how the financial performance of PT Lontar Papyrus Pulp & Paper Industry is. The research here uses qualitative research methods through descriptive analysis methods. as well as collecting information through documentation and discussions with related parties. The results of research on the Financial Performance of PT Lontar Papyrus Pulp & Paper Industry show that the current ratio of PT. LPPPI shows good conditions. Ratio The average current ratio for 3 years is 217.38%. The average value of PT LPPPI's quick ratio for the 2021-2023 period is 198.35%. The average value of PT LPPPI's cash ratio in the 2021-2023 period is 33.76%. The average value of Total Assets to Debt Ratio is 41.69%. The average value of the debt to equity ratio is 70.96%. The average value of PT LPPPI's profit margin for the 2021-2023 period is 24.84%. PT LPPPI's Return On Assets Ratio (ROA) results in the 2021-2023 period averaged 5.72%. PT LPPPI's Return on Assets Equity (ROE) ratio in the 2021-2023 period averaged 7.8%.